Keefektifan Pendekatan Direct Instruction Dalam Pelatihan Implementasi Pendidikan Literasi Humanis Bagi Guru Kelas Di Sekolah Dasar - Dina Mardiana; Sapriline Sapriline; Kuswari Kuswari; Simpun Simpun; Chairul Afif (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2021)
This study aims to analyze the effectiveness of using the direct instruction (DI) approach to improve the knowledge and skill of classroom teachers at SDN-5 Panarung and SD Muhammadiyah Pahandut Kota Palangkaraya in implementing humanist literacy education in the integrated thematic learning at the two primary schools. Ten classroom teachers at SDN-5 Panarung and SD Muhammadiyah Pahandut taken as the sample by using purposive sampling technique from the total population. This study used a quantitative method with an experimental design model of one group pretest-posttest design. The results of this study found the average grade of the Teachers ability only 61 in the pretest evaluation, then it increased to 78.5 in the posttest. Both values were statistically analyzed using t-test calculation, where the result showed t-count (2.800) is greater than t-table (1.833). Thus, it can be concluded that the DI approach is effective in increasing the knowledge and skill of classroom teachers at SDN-5 Panarung and SD Muhammadiyah Pahandut Kota Palangkaraya by implementing humanist literacy education within the integrated thematic learning at both primary schools.